Impact of Alginate on the Physicochemical Properties and Reactivity of Iron Oxides - Najem, Tarek (Université d'Ottawa / University of Ottawa, 2025)
Iron (Fe) minerals often associate with natural organic matter (OM), ranging from complex compounds like humic acids to simple ligands such as citrate and oxalate, in soils and aquatic systems. These Fe-OM interactions occur through microbial mediation, OM sorption to Fe minerals, or mineral formation in the presence of OM (coprecipitation). Such associations influence the sorption capacity of Fe minerals for foreign species (e.g., phosphate, arsenate, trace metals), their thermodynamic stability, and overall physicochemical and mineralogical characteristics. This study aimed to (1) examine how OM affects the properties and bioavailability of common Fe (oxyhydr)oxides-ferrihydrite (Fh), lepidocrocite (Lp), and goethite (Gt). These minerals were synthesized in the presence of Na-alginate (as a model OM) at C/Fe ratios of 0, 0.5, 1.0, and 1.5 mol:mol. OM notably altered mineral surface area, porosity, and crystallinity. Surprisingly, microbial Fe(III) reduction kinetics were comparable between coprecipitates and pure minerals. However, the extent of reduction varied by mineral: 2-line Fh coprecipitates showed ~15% lower reduction, whereas Lp and Gt coprecipitates exhibited only 5-7% higher reduction relative to pure minerals. These findings suggest that OM effects on Fe bioavailability are mineral-specific and more complex than previously thought, emphasizing the need to consider both mineral type and OM interactions in Fe cycling studies. To further explore the impact of additional environmental variables, the study (2) investigated how phosphate (P) sorption mode, adsorption versus coprecipitation (P/Fe 0, 0.01, and 0.1 mol:mol), influences the properties and reactivity of alginate-Fh composites (C/Fe 0 and 1.0). P-OM-Fe coprecipitates showed the highest microbial and chemical reducibility. High P loading, irrespective of sorption mode, nearly completely stabilized Fh against transformation to more crystalline phases - more effectively than alginate alone. Notably, coprecipitated P and OM together conferred added resistance to mineral transformation following biotic reduction. These findings underscore the importance of considering both OM and P, and how P is incorporated, when evaluating the environmental stability and reactivity of Fe minerals, with implications for soil fertility, contaminant mobility, and nutrient cycling. Finally, the study (3) evaluated the effect of γ-irradiation (25 kGy) as a sterilization method on OM-Fe coprecipitates. Post-irradiation, Fe(III) dissolution and reduction increased with OM content, and particle size varied based on the mineral coprecipitate type, while specific surface area and porosity were altered. Mössbauer spectroscopy revealed increased Fh crystallinity after irradiation, although bulk mineralogy remained unchanged. Interestingly, microbial reduction rates post-irradiation remained similar to untreated samples, yet the extent of Fe(III) reduction, particularly for Fh coprecipitates, increased by up to 28%. Slight increases in bioreduction were also seen for select Lp and Gt coprecipitates. These results highlight that γ-irradiation can modify key physical and chemical characteristics of Fe-OM composites, potentially skewing measurements of bioavailability and contaminant binding in sterilized samples. Taken together, these findings deepen our understanding of how OM, phosphate, and experimental treatments affect the environmental reactivity and transformation of Fe (oxyhydr)oxides. This knowledge is essential for improving models of carbon cycling under reducing conditions, and for developing strategies to manage nutrient and metal mobility in soils and sediments.
Keywords: ferrihydrite; goethite; lepidocrocite; phosphate; copecipitate; organic matter; Shewanella putrefaciens 32